2010
DOI: 10.1017/s1463423610000149
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal students’ use of and attitudes to primary care support services

Abstract: The aims of this study were to improve responses to students in distress and who are feeling suicidal, to help practitioners to increase their responsiveness to those at high risk of suicide and to develop effective responses to those affected by their deaths. The study sought to build a detailed picture of students' patterns of service use. Background: National suicide prevention strategies emphasise that suicide prevention requires the collaboration of a wide range of organisations. Among these, primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…First, to the best of our knowledge, this is the first study to examine multiple attributes of mental health literacy in UK university students. Previous studies in the UK (Chew-Graham et al, 2003;Furnham et al, 2008;Furnham et al, 2011;Furnham et al, 2013;Furnham and Wong, 2007;Stanley et al, 2010) have not addressed all major aspects of mental health literacy and therefore failed to provide a holistic investigation of what university students understand, feel about, and ultimately act on, with respect to mental health problems. Second, the MHLS, K10, and WEMWBS indicated good or excellent internal consistency, illustrating that they reliably measured all intended constructs of mental health literacy, distress, and well-being.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…First, to the best of our knowledge, this is the first study to examine multiple attributes of mental health literacy in UK university students. Previous studies in the UK (Chew-Graham et al, 2003;Furnham et al, 2008;Furnham et al, 2011;Furnham et al, 2013;Furnham and Wong, 2007;Stanley et al, 2010) have not addressed all major aspects of mental health literacy and therefore failed to provide a holistic investigation of what university students understand, feel about, and ultimately act on, with respect to mental health problems. Second, the MHLS, K10, and WEMWBS indicated good or excellent internal consistency, illustrating that they reliably measured all intended constructs of mental health literacy, distress, and well-being.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Research has shown that as a group, young people are generally likely to make low use of health and other professional support services (Viner and Barker, 2005) and are more likely to turn to their friends or other informal sources of help when facing a crisis (Aseltine and DeMartino, 2004;Elias, 1994, 1995;Hawton et al, 2002). Scepticism about the effectiveness of intervention and limited experience of accessing professional services on their own account may make them more likely to turn to informal rather than formal sources of help, including the internet (Oliver and Storey, 2006;Stanley et al, 2010). Young people can find relief and comfort in discovering that they are not alone, that there are others who are undergoing a similar kind of pain or suffering along with them (Ozawa-de Silva, 2008).…”
Section: Implications For Practice Intervention and Preventionmentioning
confidence: 99%
“…An alarmingly common theme in the research is the reluctance of young university students with mental health concerns to engage in help-seeking behaviours. This is particularly concerning considering recent research conducted by Stanley, Mallon, Bell, and Manthorpe (2010) found that failure to engage with support services could have been a primary factor in completed suicides of students in higher education. This lack of student engagement was apparent in a large survey of college students in the United States, where 67% perceived a need for mental health services but only 38% had sought such services in the preceding year (Cranford, Eisenberg, & Serras, 2009).…”
Section: Help-seeking Behaviourmentioning
confidence: 99%
“…Strategies and interventions to address the concerning prevalence of mental illness in university students have been widely discussed, and universities have a clear responsibility to adopt evidence-based support services to promote the mental health and wellbeing of students and, in turn, encourage their academic success. Stanley, Mallon, Bell, and Manthorpe (2010) highlighted the need for specialist mental health advisors within Universities to link more strategically with general practitioners and primary care providers. Open communication and collaboration between students and staff, and the availability of enhanced mental health services, is considered key to preventing worsening psychopathology of students and improving student retention (Schwartz & Kay, 2009).…”
Section: Treatment and Interventionsmentioning
confidence: 99%